Needs Analysis for Developing a Fractions Learning Module Based on Local Wisdom to Strengthen Elementary School Students’ Conceptual Understanding - Rusmawati, Rina; Mardiyana, Mardiyana; Supianto, Supianto (Universitas Sebelas Maret, 2026)
Numeracy skills in elementary school need early strengthening. Fractions are a critical topic because students must understand parts of a whole, build representations, and apply ideas in context. This study aimed to analyze the needs for developing a local wisdom based fractions learning module to strengthen Grade IV students’ conceptual understanding in elementary schools in Nguntoronadi District. The study used a qualitative approach with a descriptive design. It was conducted in five elementary schools. Participants included Grade IV teachers (n = 5) and Grade IV students (n = 50). Data were collected through teacher and student questionnaires covering seven module need indicators. Open ended items were used to explore participants’ experiences, difficulties, and expectations. Data were analyzed interactively through data reduction, data display, and conclusion drawing. Source triangulation was applied by comparing teacher and student responses on the same indicators. The results show that students’ conceptual understanding of fractions is still uneven. The highest difficulties occur in comparing fractions, identifying equivalent fractions, and solving word problems. Both teachers and students need a module that integrates local wisdom contexts, uses simple language, provides detailed step by step instructions, includes concept summaries, offers graduated practice, provides brief understanding checks, and delivers clear feedback. Teachers and students are generally ready to use the module, but the module should remain flexible due to limited instructional time